Synthetic GM1 improves motor and memory dysfunctions in mice with monoallelic or biallelic disruption of GM3 synthase - Suman Chowdhury; Ranjeet Kumar; Evelyn Zepeda; Shawn DeFrees; Robert Ledeen (FEBS Open Bio, 2023)
This study attempts to answer the question of whether mice with biallelic and monoallelic disruption of the St3gal5 (GM3 synthase) gene might benefit from GM1 replacement therapy. The GM3 produced by this sialyltransferase gives rise to downstream GD3 and the ganglio‐series of gangliosides. The latter includes the a‐series (GM1 + GD1a), which has proved most essential for neuron survival and function (especially GM1, for which GD1a provides a reserve pool). These biallelic mice serve as a model for children with this relatively rare autosomal recessive condition (ST3GAL5−/−) who suffer rapid neurological decline including motor loss, intellectual disability, visual and hearing loss, failure to thrive, and other severe conditions leading to an early death by 2–5 years of age without supportive care. Here, we studied both these mice, which serve as a model for the parents and close relatives of these children who are likely to suffer long‐term disabilities due to partial deficiency of GM1, including Parkinson's disease (PD). We find that the movement and memory disorders manifested by both types of mice can be resolved with GM1 application. This suggests the potential therapeutic value of GM1 for disorders stemming from GM1 deficiency, including GM3 synthase deficiency and PD. It was noteworthy that the GM1 employed in these studies was synthetic rather than animal brain‐derived, reaffirming the therapeutic efficacy of the former.